Investigation into the visual perceptive ability of anaesthetists during ultrasound-guided interscalene and femoral blocks conducted on soft embalmed cadavers: a randomised single-blind study. (April 2018) - Mustafa, A.; Seeley, J.; Munirama, S.; Columb, M.; McKendrick, M.; Schwab, A.; Corner, G.; Eisma, R.; Mcleod, G.
Abstract: Background: Errors may occur during regional anaesthesia whilst searching for nerves, needle tips, and test doses. Poor visual search impacts on decision making, clinical intervention, and patient safety. Methods: We conducted a randomised single-blind study in a single university hospital. Twenty trainees and two consultants examined the paired B-mode and fused B-mode and elastography video recordings of 24 interscalene and 24 femoral blocks conducted on two soft embalmed cadavers. Perineural injection was randomised equally to 0.25, 0.5, and 1.0 ml volumes. Tissue displacement perceived on both imaging modalities was defined as 'target' or 'distractor'. Our primary objective was to test the anaesthetists' perception of the number and proportion of targets and distractors on B-mode and fused elastography videos collected during femoral and sciatic nerve block on soft embalmed cadavers. Our secondary objectives were to determine the differences between novices and experts, and between test-dose volumes, and to measure the area and brightness of spread and strain patterns. Results: All anaesthetists recognised perineural spread using 0.25 ml volumes. Distractor patterns were recognised in 133 (12%) of B-mode and in 403 (38%) of fused B-mode and elastography patterns; P <0.001. With elastography, novice recognition improved from 12 to 37% ( P <0.001), and consultant recognition increased from 24 to 53%; P <0.001. Distractor recognition improved from 8 to 31% using 0.25 ml volumes ( P <0.001), and from 15 to 45% using 1 ml volumes ( P <0.001). Conclusions: Visual search improved with fusion elastography, increased volume, and consultants. A need exists to investigate image search strategies.